The potential of virtual global mobility: implications for practice and future research - Selmer, Jan; Dickmann, Michael; Froese, Fabian J.; Lauring, Jakob; Reiche, B. Sebastian; Shaffer, Margaret (Emerald, 2021)
Purpose The COVID-19 pandemic has forced global organizations to adopt technology-driven virtual solutions involving faster, less costly and more effective ways to work worldwide even after the pandemic. One potential outcome may be through virtual global mobility (VGM), defined as the replacement of personal physical international interactions for work purposes with electronic personal online interactions. The purpose of this article is to establish VGM as a theoretical concept and explore to what extent it can replace or complement physical global work assignments. Design/methodology/approach This perspectives article first explores advantages and disadvantages of global virtual work and then discusses the implementation of VGM and analyses to what extent and how VGM can replace and complement physical global mobility. Findings Representing a change of trend, long-term corporate expatriates could become necessary core players in VGM activities while the increase of the number of global travelers may be halted or reversed. VGM activities will grow and further develop due to a continued rapid development of communication and coordination technologies. Consequently, VGM is here to stay! Originality/value The authors have witnessed a massive trend of increasing physical global mobility where individuals have crossed international borders to conduct work. The authors are now observing the emergence of a counter-trend: instead of moving people to their work the authors often see organizations moving work to people. This article has explored some of the advantages, disadvantages, facilitators and barriers of such global virtual work. Given the various purposes of global work the authors chart the suitability of VGM to fulfill these organizational objectives.
Keywords: Virtual Global Mobility (VGM); Global virtual work; Expatriates; Global travellers; Global work assignment purposes